Immunotherapy: CARs on the fast-track to treat cancer - Fraietta, Joseph A. (Henry Stewart Talks, 2021)
History of immunotherapy, Current status of CAR T cell therapy, Synthetic biology: The nuts and bolts of CARs, CAR T cell manufacturing process, CAR T cell successes, CAR T cell limitations, CAR T cell therapy in solid tumors, The promise of universal CAR, The future of CAR T cell therapies